ANALISIS KETERAMPILAN BERPIKIR KRITIS SISWA DAN FAKTOR-FAKTOR YANG MEMPENGARUHINYA PADA SEKOLAH MENENGAH KEJURUAN NEGERI 5 MAKASSAR - Susanto; Muhammad Ardi; Anas Arfandi (UNM Journal of Technology and Vocational, 2025)
Susanto, 2023. Analysis of Students' Critical Thinking Skills and Its Influencing Factors at Vocational High School 5 Makassar. Thesis. Technology and Vocational Education, Postgraduate Program. State University of Makassar. (supervised by Muhammad Ardi and Anas Arfandi). This type of study is quantitative research using a correlational approach which aims to examine the level of critical thinking skills, students’ achievement motivation, students’ family environment, teacher’s teaching methods, and students’ learning attitudes at SMKN 5 Makassar, examine the effect of students’ achievement motivation, students’ family environment, teacher’s teaching methods, and students' learning attitudes on the students’ critical thinking skills at SMKN 5 Makassar. The population of the study were all grade XI students of the Construction and Property Technology Expertise Program at SMKN 5 Makassar. The sampling technique employed random sampling. The results of the study reveal that the level of students' critical thinking skills is 50.85% which is in high category. The students’ achievement motivation is in high category with 50.85%, the family environment is in high category with 50.85%, the teacher’s teaching methods is in high category with 59.32%, and the students' learning attitudes are in high category with 54.24%. The students’ achievement motivation, family environment, teacher’s teaching methods, and students’ learning attitudes collectively influence Y by 72.2%. Keywords: Critical Thinking Skills, Motivation for Achievement, Family Environment, Teacher Teaching Methods, Student Learning Attitudes